Laboratory Biorisk Management Manual : Faculty of Medicine and Health Science, 6th October 2016 - Faculty of Medicine and Health Science, Universiti Malaysia Sarawak (Faculty of Medicine and Health Sciences, UNIMAS, 2016)
The Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak is proud to launch its own Biorisk Management Manual. The development of this manual was part of project (GTRX-14-60789-0) to Dr. Tan Cheng Siang under the Biosecurity Malaysia Enhancement Grant (BMEG) from the Biosecurity Engagement Program (BEP) US Department of State which was executed via CRDF Global. The Biorisk Management Manual was carefully written by the Faculty’s Biorisk Management Manual Committee and was based on the internationally recognized CWA15793 document. The manual provides a management system for both biosafety and biosecurity aspect and hope to help the Faculty of Medicine and Health Sciences to spearhead biorisk management in UNIMAS and beyond. I believe the launching of our Faculty’s Biorisk Management Manual in timely with the global development in biosafety and biosecurity.